Diagnostic accuracy of optical coherence tomography for assessing surgical margins of canine soft tissue sarcomas in observers of different specialties. Issue 1 (11th September 2020) - Dornbusch, Josephine A.; Selmic, Laura E.; Huang, Pin‐Chieh; Samuelson, Jonathan P.; McLaughlin, Eric M.; Wavreille, Vincent A.; Ogden, Jessica A.; Abrams, Brittany; Kalamaras, Alex; Green, Eric; Hostnik, Eric T.; Every, Lincoln; et al.
Abstract: Objective: To determine the diagnostic accuracy of optical coherence tomography (OCT) to assess surgical margins of canine soft tissue sarcoma (STS) and determine the influence of observer specialty and training. Study design: Blinded clinical prospective study. Animals: Twenty‐five dogs undergoing surgical excision of STS. Methods: In vivo and ex vivo surgical margins were imaged with OCT after tumor resection. Representative images and videos were used to generate a training presentation and data sets. These were completed by 16 observers of four specialties (surgery, radiology, pathology, and OCT researchers). Images and videos from data sets were classified as cancerous or noncancerous. Results: The overall sensitivity and specificity were 88.2% and 92.8%, respectively, for in vivo tissues and 82.5% and 93.3%, respectively, for ex vivo specimens. The overall accurate classification for all specimens was 91.4% in vivo and 89.5% ex vivo. There was no difference in accuracy of interpretation of OCT imaging by observers of different specialties or experience levels. Conclusion: Use of OCT to accurately assess surgical margins after STS excision was associated with a high sensitivity and specificity among various specialties. Personnel of all specialties and experience levels could effectively be trained to interpret OCT imaging. Clinical significance: Optical coherence tomography can be used by personnel of different specialty experience levels and from various specialties to accurately identify canine STS in vivo and ex vivo after a short training session. These encouraging results provide evidence to justify further research to assess the ability of OCT to provide real‐time assessments of surgical margins and its applicability to other neoplasms.